Clinical antiangiogenic effect of recombinant adenovirus-p53 combined with hyperthermia for advanced cancer - Li, Xiaofan; Xiao, Shaowen; Li, Yongheng; Zhang, Shanwen (Chinese Journal of Cancer Research; Vol 25, No 6 (December 26, 2013): Chinese Journal of Cancer Research, 2013)
Objective: To assess the safety and clinical antiangiogenic effect of recombinant adenovirus-p53 (rAd-p53) combined with hyperthermia plus or not plus radiotherapy in advanced cancer. Methods: Expression of Vascular epithelial growth factor (VEGF) after intratumoral injection of rAd-p53 was assayed by immunohistochemistry (IHC) imaging. Forty-four patients with advanced cancer were enrolled into this clinical study. The patients were intratumorally injected with rAd-p53 (Gendicine) at a dose of 1×1012 vp once a week, with a total of 4-54 (mean 7.7) times. Total of 4-29 (mean 8.5) times of hyperthermia was given to the patients. Among the 44 patients, 30 patients were concurrently added with radiotherapy of a total dose 30-76 Gy/15-38 f/3-8 w (mean 58 Gy). Results: Before and after intratumoral injection of rAd-p53, the VEGF IHC positive cell scores were 2.80 and 1.50, respectively (P=0.031). The treatment of rAd-p53 combined with hyperthermia plus or not plus radiotherapy in advanced cancer achieved CR rate of 13.60% (6/44), and PR rate of 29.6% (13/44), and thus the effective rate was 43.2%. In addition to 6 patients with CR, 19 patients (19/38, 50.0%) had low density area (LDA) of more than 50% area on CT image within tumor indicating tumor tissue necrosis. Conclusions: Our data indicate that rAd-p53 inhibits VEGF expression and angiogenesis, and promotes tumor necrosis and shrinkage induced by hyperthermia plus or not plus radiotherapy in advanced cancer.